Clinical characteristics and outcomes for paediatric patients admitted with congenital or acquired syphilis: a population-based cohort study. Issue 8 (20th May 2020) - Brock, Robert; Edwards, Brett; Lu, Shengjie; Chu, Angel; Somayaji, Ranjani
Abstract : Objectives: Paediatric congenital and acquired syphilis cases have been increasing since 2012 in the USA. Potential differences in associated hospitalisation trends and healthcare utilisation between the two syphilis entities have not yet been assessed. We sought to compare these entities and describe their clinical characteristics, distribution and impact in the USA. Methods: We conducted a population-based cohort study using the 2016 Kids' Inpatient Database (KID) to identify and characterise syphilis-associated hospitalisations among paediatric patients (age 0–21 years) in the USA during the year of 2016. Length of stay and hospitalisation costs for patients with congenital and acquired syphilis were compared in multivariable models. Results: A total of 1226 hospitalisations with the diagnosis of syphilis were identified. Of these patients, 958 had congenital syphilis and 268 were acquired cases. The mean cost of care for congenital syphilis was 23 644 (SD=1727), while the treatment of a patient with acquired syphilis on average cost 10 749 (SD=1966). Mean length of stay was 8 days greater and mean total costs were 12 895 (US dollars) higher in the congenital syphilis cohort compared with the acquired syphilis cohort. In congenital syphilis, there were greater frequency of cases in the Southern and Western regions of the USA (p<0.001). Conclusion: Congenital syphilis was associated with greater healthcare-related expenditure than acquired syphilis in paediatric patients. In addition to improving patient outcomes, congenital syphilis prevention efforts may significantly reduce healthcare utilisation burden and cost.